2004
DOI: 10.1111/j.1478-3231.2004.0958.x
|View full text |Cite
|
Sign up to set email alerts
|

Loss of cooperative function of transforming growth factor‐β signaling proteins, smad3 with embryonic liver fodrin, a β‐spectrin, in primary biliary cirrhosis

Abstract: These results suggest that a compromised cytoarchitecture and polarized trafficking of TGF-beta signaling molecules, ELF and Smad3 are involved in the pathogenesis of PBC as well as HCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 30 publications
0
27
1
Order By: Relevance
“…Subsequent work has shown that Dab2 acts as a critical switch of TGFβ-induced EMT (53). Additionally, TGFβ receptor-associated protein-1 (TRAP-1) (54), and the adaptor protein embryonic liver fodrin (ELF) (55) enable activation of R-Smads by the activated TGFβ receptor complex. Endocytosis of the active TGFβ receptor complex is another mechanism by which R-Smad activation is regulated.…”
Section: Canonical Tgfβ Signaling Pathwaymentioning
confidence: 99%
“…Subsequent work has shown that Dab2 acts as a critical switch of TGFβ-induced EMT (53). Additionally, TGFβ receptor-associated protein-1 (TRAP-1) (54), and the adaptor protein embryonic liver fodrin (ELF) (55) enable activation of R-Smads by the activated TGFβ receptor complex. Endocytosis of the active TGFβ receptor complex is another mechanism by which R-Smad activation is regulated.…”
Section: Canonical Tgfβ Signaling Pathwaymentioning
confidence: 99%
“…Gut development occurs through an interaction of two key signaling pathways, the TGF-b (Sporn and Roberts, 1988Roberts, , 1990Moses et al, 1991;Liu et al, 2004;Seoane et al, 2004) and Wnt signaling pathways as well as transcriptional regulators of endoderm formation, such as members of the fibroblast growth factors (FGF), Gata, and Forkhead transcription factor families (Wells and Melton, 1999;Matsumoto et al, 2002;Stainier, 2002Stainier, , 2005Mishra et al, 2004). Remarkably, this complex sequence of signals is highly conserved across the phyla from Caenorhabditis elegans, Drosophila, sea urchins, ascidians, Xenopus, zebrafish, the chick, and the mouse (Clements et al, 2001).…”
Section: Identifying Adult Gastrointestinal Stem Cellsmentioning
confidence: 99%
“…Hepatoblasts express alphafetoprotein (AFP) and albumin and later both hepatocyte (AFP) and biliary (cytokeratins 7 and 19) lineages. In adult human tissues, these hepatic progenitor cells (or mouse oval cells) are immature epithelial cells found residing in the smallest terminal branches of the biliary tree, the canals of Hering, that connect the interhepatocytic bile canaliculi with the bile ducts in the portal tract (Roskams et al, 2003;Mishra et al, 2004). In hepatocarcinogenesis, human hepatic progenitor cells can give rise to hepatocellular carcinoma as well as cholangiocarcinomas (Shafritz and Hadziyannis, 1987;Theise et al, 1999).…”
Section: Identifying Adult Gastrointestinal Stem Cellsmentioning
confidence: 99%
“…The mislocalization of ELF was observed in Smad2 +/ /Smad3 +/ mutants. These data suggest that ELF and SMAD3 are involved in the pathogenesis of PBC [41]. Interestingly, an exacerbated phenotype of early gastric hyperplasia, ectasia, foveolar gland dysplasia, and hamartomas with obstructing tumors at the antrum and pylorus were developed in 90% of the elf +/ /Smad4 +/ heterozygous mutants.…”
Section: Spectrin and The Cell Cyclementioning
confidence: 76%